Online Optical Tomography System Application of Charge-Coupled Device (CCD) for Object Detection in Crystal Clear Water - Juliza Jamaludin; Ruzairi Abdul Rahim; Herlina Binti Abdul Rahim; Mohd Hafiz Fazalul Rahiman; Siti Zarina Mohd Muji; Jemmy Mohd Rohani (Shaheed Zulfiqar Ali Bhutto Institute of Science and Technology, 2024)
Journal of Independent Studies and Research – Computing Volume 14 Issue 1 Jan-June 2016